Evaluación del sistema de puesta a tierra de la línea de subtransmisión Ambato -Samanga y Samaga- Pillaro a 69 KV perteneciente a la Empresa Eléctrica Ambato para proponer alternativas que permitan mejorar el sistema. - Chiliquinga Taipe, Johana Gabriela (2017)
The present investigation contains a diagnosis of the present situation of the systems of ground of the structures of the lines of Subtransmission to 69 KV. Ambato - Samanga and Samanga - Pillaro which has a length of 7,133 Km. For this work a collection of information of each one of the structures was carried out in a stacking sheet, afterwards measurements of ground resistance and the resistivity of the soil of each one of the structures were made, defining the specific zones to the Along the trajectory, using equipment such as the Megger DET24C Digital Earth Clamp and the Telurometro The Digital Ground Resistance Tester Model 4500. In addition, there were identified structures that do not have earthing and some that have problems by cutting the cable In the path to the earthing electrode. Once the measurements were analyzed it was possible to conclude that some structures do not have a standards recommended ground resistance value of 20 ohm for Subtransmission lines. Proposals were analyzed that allow these structures to reach the recommended value. Therefore, an economic analysis of each of the proposals was made to identify which of them is the most economical and most technically feasible, being determined that the incorporation of counterweights and the provision of a vertical electrode are the most technically and economically feasible. Finally, it was recommended that the proposed proposals be analyzed for their later implementation in the short term, as this would allow the Ambato Electric Company to guarantee the safety of people, animals and electrical equipment in the event of a disturbance in the electrical system and require an adequate functioning of the Grounding systems.